2022
DOI: 10.2186/jpr.jpr_d_20_00262
|View full text |Cite
|
Sign up to set email alerts
|

Socket shield technique: A systemic review and meta-analysis

Abstract: The aim of the present study was to evaluate the clinical feasibility of the socket shield technique (SST). Study selection: An electronic search of the PubMed, Cochrane Central Register of Controlled Trials, and Wiley Online Library databases, and a manual reference search for articles published up to September 2020 was conducted. Meta-analysis was performed to estimate marginal bone loss (MBL), changes in buccal bone width (cBBW), pink esthetic score (PES), implant stability quotient (ISQ), implant failure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The socket shield technique (SST) suggests partial root retention on the buccal aspect during tooth extraction with subsequent immediate implant placement [ 3 ]. This technique is technically demanding and time intensive, and the feasibility of SST had yet to established as the potential clinical benefits of SST lack strong scientific evidence [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The socket shield technique (SST) suggests partial root retention on the buccal aspect during tooth extraction with subsequent immediate implant placement [ 3 ]. This technique is technically demanding and time intensive, and the feasibility of SST had yet to established as the potential clinical benefits of SST lack strong scientific evidence [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 Nevertheless, it should not be used as a daily-routine clinical procedure due to its technical sensitivity and lack of evidence-based consensus guidelines, and long-term follow-up data. [20][21] Moreover, the socket-shield technique, as all the minimally invasive surgical procedures, due to limited access and view of the operative field, required substantial surgical skills, to carve the buccal and remove the palatal and apical portions of the root, positioning at the same time an implant in the alveolar socket in respect of the surgical and prosthetic requirements. To reduce the risk of root exposure, a socket-shield with smooth margin, free of sharp edges, connected to the bundle bone with a sound periodontal attachment with its vascularization properly maintained, is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen patients (6 males and 12 females; mean age 52.54 ± 4.92 years; range 33-72 years) were consecutively enrolled, treated, followed up for at least 1 year after the definitive prosthesis Recently, two systematic reviews with meta-analysis reported on the socket-shield technique. [20][21] Short-term favorable outcomes can be expected in terms of buccal bone plate width and height changes, MBL and esthetic outcomes. Comparable complication and implant failure rates following immediate implant placement with or without socket-shield were reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations